"Bringing heaven down to earth": the purpose and place of religion in UK food aid. Issue 3 (7th August 2017) - Power, Madeleine; Small, Neil; Doherty, Bob; Stewart-Knox, Barbara; Pickett, Kate E.
Abstract : Purpose: This paper uses data from a city with a multi-ethnic, multi-faith population to better understand faith-based food aid. The paper aims to understand what constitutes faith-based responses to food insecurity, compare the prevalence and nature of faith-based food aid across different religions and explore how community food aid meets the needs of a multi-ethnic, multi-faith population. Design/methodology/approach: The study involved two phases of primary research. In Phase 1, desk-based research and dialogue with stakeholders in local food security programmes were used to identify faith-based responses to food insecurity. Phase 2 consisted of 18 semi-structured interviews involving faith-based and secular charitable food aid organizations. Findings: The paper illustrates the internal heterogeneity of faith-based food aid. Faith-based food aid is highly prevalent and the vast majority is Christian. Doctrine is a key motivation among Christian organizations for their provision of food. The fact that the clients at faith-based, particularly Christian, food aid did not reflect the local religious demographic is a cause for concern in light of the entry-barriers identified. This concern is heightened by the co-option of faith-based organizations by the state as part of the "Big Society" agenda. Originality/value: This is the first academic study in the UK to look at the faith-based arrangements of Christian and Muslim food aid providers, to set out what it means to provide faith-based food aid in the UK and to explore how faith-based food aid interacts with people of other religions and no religion.